Предмет: Математика, автор: 6GodMod9

-2 1/6:(-2,6)+(-3 4/15•6/7)-3=​

Ответы

Автор ответа: rexzyyy
1

Ответ:

\frac{19}{30}

Пошаговое объяснение:

-2\frac{1}{6} +(-2,6)+(3\frac{4}{15} * \frac{6}{7})-3 = -\frac{13}{6} : (-\frac{13}{5})+(\frac{49}{15} * \frac{6}{7})-3=\frac{13}{6} * \frac{5}{13} + (\frac{7}{5}*2)-3=\frac{1}{6} * 5 + \frac{14}{5} -3= \frac{5}{6} + \frac{14}{5} -3 = \frac{25+84-90}{30} = \frac{19}{30}

Автор ответа: Robyy
0

Ответ:

-2 1/6:(-2,6)+(-3 4/15*6/7)-3=-13/6:(-13/5):(-49/15*6/7) - 3=13/6*5/13+(-7/5*2) - 3=5/6-14/5-3=149/30

Пошаговое объяснение:

*- це множення

Похожие вопросы
Предмет: Химия, автор: Влад11737463